Penerapan Terapi Musik Gamelan Terhadap Penurunan Intensitas Nyeri Post Operasi Di Ruang Intensive Care Unit RSUD Pandan Arang Boyolali - Elmatiana Elmatiana; Fida’ Husain; Panggah Widodo (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: The prevalence of extreme pain in medical and surgical patients admitted to the Intensive Care Unit (ICU) is more than 80.0%. One of the nonpharmacological therapies that can be used to control pain is the distraction technique with music therapy, where this application uses gamelan music therapy. Objective: To determine the results of the implementation of gamelan music therapy to reduce postoperative pain intensity in the Intensive Care Unit of Pandan Arang Hospital Boyolali. Method: The design used in this application is using a descriptive case study approach. Application is carried out for 30 minutes 2x a day in 4 consecutive days. Findings: Comparison of the final results of application showed that on the 4th day after the implementation of the VDS scale the two respondents were the same, namely on the pain scale 3. The results of the CPOT scale on the 4th day of Mrs. W after implementation are a scale of 4. The results of the CPOT scale on the 4th day of Mrs. S after implementation are a scale of 3. Implication: From the final results of the application before and after it can be concluded that gamelan music therapy can reduce the intensity of pain in postoperative patients in the ICU of Pandan Arang Hospital Boyolali.